ASSOCIATIONS BETWEEN ANKLE INSTABILITY AND WEIGHT DISTRIBUTION IN THE FEET - Kuzminas, Emilis; Komžienė, Ramunė; Markauskienė, Asta; Žukauskienė, Milda (PROFESSIONAL STUDIES: Theory And Practice, 2023)
Damage of the ankle ligaments is a common injury that, if untreated or sustained repeatedly, can lead to chronic ankle joint instability. The aim of the study was to evaluate the associations between ankle instability and plantar pressure distribution. 20 physically active, young people underwent a plantar pressure measurement on a treadmill with an integrated sensor system. When the results were compared it was discovered that higher plantar pressure was found in the outer part of the foot when standing, walking, and running in unstable ankles and less pressure distribution in the inner part of the foot.